A novel hybrid backscatter and conventional algorithm for multi‐hop Internet of Things networks. Issue 12 (2nd September 2022) - Raeisi, Mahmoud; Mahdavi, Mehdi; Doost Hosseini, Ali Mohammad
Abstract: This article investigates a multi‐hop cognitive radio network in terms of end‐to‐end bit delivery. The network exploits backscatter communication (BackCom) and harvest‐then‐transmit (HTT) mode in a hybrid manner. Such a network can be used in Internet of Things (IoT) applications in which IoT users coexist with a primary network and use the primary spectrum to transmit data in both BackCom and HTT modes. Besides, such users can harvest energy from the primary signals. A novel hybrid backscatter and conventional transmission (HBCT) algorithm is proposed in order to maximize end‐to‐end bit delivery by jointly optimizing time and power allocations. For this goal, we formulate a nonconvex optimization problem. Next, we transform the problem into a convex one and develop a new analytical formulation by which we calculate the optimal power and time allocation in closed‐form equations. The numerical results demonstrate the superiority of HBCT compared with current schemes. Abstract : Integrating backscatter communication (BackCom) and cognitive radio technique is promising for the next generation wireless communication networks since they can efficiently improve performance and use the primary spectrum concurrently. This article shows that BackCom and cognitive radio can work together in a multi‐hop network and improve the network's performance.